From the archives of Levon Mkrtchyan (Levon Mkrtchyan’s work on the book "Anna Akhmatova. Life and Translations") - SAHAKYANC, KARINE (Bulletin of Yerevan University H: Russian Philology, 2021)
The archive of Professor of Yerevan State University, Academician at the National Academy of Sciences of the Republic of Armenia L. M. Mkrtchyan (1933-2001) preserves a large amount of materials valuable for the illustration of the Armenian-Russian literary connections in the second half of the XX century. A folder stands out among these materials, titled "Work on Akhmatova". This work started at the end of 1980s, when L. Mkrtchyan was offered to compile and write an introduction to the second volume (Translations) of the two-volume edition of A. Akhmatova’s works, planned to be published in the frames of the well known series "Poet’s Library" (Leningrad Branch). Due to the crisis in book edition on the edge of the 80-s and 90-s, the plan of "Poet’s Library" was not fulfilled. Nevertheless, the work carried out by L. Mkrtchyan appeared in the author’s edition of a small book, developed from the introduction (1992). The archive materials, published in the present article, reflect the process, conditions, level and evaluation of the "work on Akhmatova" by L. Mkrtchyan.